# Solve using the Square Root Property 2x^2-13x-2=0 2×2-13x-2=0
Use the quadratic formula to find the solutions.
-b±b2-4(ac)2a
Substitute the values a=2, b=-13, and c=-2 into the quadratic formula and solve for x.
13±(-13)2-4⋅(2⋅-2)2⋅2
Simplify.
Simplify the numerator.
Raise -13 to the power of 2.
x=13±169-4⋅(2⋅-2)2⋅2
Multiply 2 by -2.
x=13±169-4⋅-42⋅2
Multiply -4 by -4.
x=13±169+162⋅2
Add 169 and 16.
x=13±1852⋅2
x=13±1852⋅2
Multiply 2 by 2.
x=13±1854
x=13±1854
Simplify the expression to solve for the + portion of the ±.
Simplify the numerator.
Raise -13 to the power of 2.
x=13±169-4⋅(2⋅-2)2⋅2
Multiply 2 by -2.
x=13±169-4⋅-42⋅2
Multiply -4 by -4.
x=13±169+162⋅2
Add 169 and 16.
x=13±1852⋅2
x=13±1852⋅2
Multiply 2 by 2.
x=13±1854
Change the ± to +.
x=13+1854
x=13+1854
Simplify the expression to solve for the – portion of the ±.
Simplify the numerator.
Raise -13 to the power of 2.
x=13±169-4⋅(2⋅-2)2⋅2
Multiply 2 by -2.
x=13±169-4⋅-42⋅2
Multiply -4 by -4.
x=13±169+162⋅2
Add 169 and 16.
x=13±1852⋅2
x=13±1852⋅2
Multiply 2 by 2.
x=13±1854
Change the ± to -.
x=13-1854
x=13-1854
The final answer is the combination of both solutions.
x=13+1854,13-1854
The result can be shown in multiple forms.
Exact Form:
x=13+1854,13-1854
Decimal Form:
x=6.65036762…,-0.15036762…
Solve using the Square Root Property 2x^2-13x-2=0   ## Download our App from the store

### Create a High Performed UI/UX Design from a Silicon Valley.  Scroll to top